Valuation uncertainty at times of market unrest : Tesla case study - Brieda, Vladimír; Taušer, Josef; Zezula, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The valuation of a company is typically determined by its expected future cash flows, which can be difficult to predict during market instability. This uncertainty can make it challenging to value a company accurately and create risks for investors. Therefore, it is essential for analysts to carefully consider the potential impact of market unrest on a company's valuation. By examining the possibilities during uncertain times in the case of a particular company - Tesla, Inc., this thesis aims to provide valuable insights for investors and analysts looking to navigate the challenges of valuing a company in a volatile market. This may involve using various valuation methods and sensitivity analyses to account for potential outcomes. Additionally, analysts should consider other factors that may affect the company's valuation, such as its competitive position and the potential for future growth.
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses